Introducing MakingJusticeWork.org: Connecting knowledge, strengthening justice - International Federation for Human Rights (International Federation for Human Rights, 2025)
On the European Union (EU) Day Against Impunity for Genocide, Crimes Against Humanity and War Crimes, the Global Initiative Against Impunity for International Crimes and Serious Human Rights Violations (GIAI) launches MakingJusticeWork.org, a digital platform designed to strengthen the work of key stakeholders and actors engaged in the fight for accountability.
Worldwide